Aliran Barnāsiyah dalam Kesusatraan Arab: Kajian Historis - Ridwan Ritonga; Raden Muhammad Ardiansyah Kurniawan (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This study aims to investigate and reveal the role of Parnassianism in the development of Arabic literature. Parnassianism, which originated in France in the 19th century, emphasized formal beauty, clarity, and technical rigor in literary works, while rejecting the excessive use of emotional expression. This research shows how the influence of Parnassianism has permeated the works of prominent Arabic literati, influencing writing style, poetry structure, and themes raised. Through historical approaches and comparative literary analysis, this study traces the presence of Parnassianism in the works of Arab literati, from the introduction of Parnassian aesthetic concepts to their application in the context of Arabic literature. The works of Arabic literati such as Aḥmad Syawqῑ, Ḥāfiẓ Ibrāhῑm, and others are explored to highlight the formal use of Parnassianism and how it influenced the evolution of modern poetry in the context of Buddhism.